ChemInform Abstract: Ligand‐Accelerating Low‐Loading Copper‐Catalyzed Effective Synthesis of (E)‐1, 3‐Enynes by Coupling Between Vinyl Halides and Alkynes Performed in Water. Issue 50 (10th December 2013) - Sun, Peng; Yan, Hong; Lu, Linhua; Liu, Defu; Rong, Guangwei; Mao, Jincheng
Abstract The title reaction provides best results when vinyl bromides are used as substrates, whereas vinyl chlorides and iodides give low yields of the desired products.